Picture perfect during a pandemic? Body image concerns and depressive symptoms in U.S. adolescent girls during the COVID-19 lockdown. Issue 4 (2nd October 2022) - Choukas-Bradley, Sophia; Maheux, Anne J.; Roberts, Savannah R.; Hutchinson, Emily A.; Lu, Celine; Ladouceur, Cecile D.; Silk, Jennifer S.
ABSTRACT: The stay-at-home orders of the COVID-19 pandemic disrupted U.S. adolescents' lives in numerous ways during the spring of 2020, including substantial changes to in-person routines and increased reliance on digital media. For adolescent girls, stay-at-home practices may have implications for body image concerns. In this research brief, we examine adolescent girls' pandemic-related body image concerns and longitudinal associations with depressive symptoms. The sample included 93 U.S. adolescent girls ( M age = 15.01; 68.8% White), with approximately 2/3 at temperamental risk for depression. Participants self-reported their depressive symptoms and pandemic-related body image concerns via online surveys at three assessments: Time 1 occurred in April/May 2020, approximately one month into stay-at-home orders, followed by two-week and seven-month follow-up assessments. Two pandemic-related body image concerns were assessed: (1) concerns about disrupted appearance-management routines and (2) evaluating one's appearance on video-chat. Both forms of pandemic-related body image concerns predicted depressive symptoms two weeks later, and concerns about disrupted routines also predicted depressive symptoms seven months later. In an era of social distancing, frequent technology-based interactions, and disrupted routines, future work should continue to investigate adolescents' body image concerns and the implications for longer-term mental health outcomes. IMPACT SUMMARY: Prior State of Knowledge : The spring 2020 COVID-19 lockdown substantially disrupted U.S. adolescents' lives. Prior research indicated that disruptions related to stay-at-home orders may have increased some adults' body image concerns. Additionally, research pre-pandemic linked body image concerns with adolescent girls' depressive symptoms. Novel Contributions : We found that two pandemic-related body image concerns – evaluating one's appearance on video-chat, and concerns about changes to appearance through disruptions in routines (e.g. gym and salon closures) – were associated with higher depressive symptoms among U.S. adolescent girls. Practical Implications : Parents and practitioners should assess whether adolescent girls are experiencing distress related to disrupted routines and increased video-chat use. Policymakers should continue to consider the best strategies for mitigating negative social media effects on girls' body image and depressive symptoms.